Increased QT dispersion in epileptic children - AKALIN, FİGEN (WILEY, 2003)
Aim: Epilepsy is a common paroxysmal disorder in childhood. Tachyarrhythmia, bradyarrhythmia, asystole, atrioventricular block, ventricular fibrillation or sudden death may occur during seizures. Mutations of ion-channel coding genes are found in patients with idiopathic or cryptogenic epilepsy. The ion channels also play a role in arrhythmogenesis. QT dispersion is a non-invasive method for assessment of regional repolarization differences within the myocardial tissue. This study investigated QT and QTc dispersion (QTcd) and the risk of dysrhythmia in epileptic children. Methods: The first group included 28 patients with newly diagnosed epilepsy and not taking antiepileptic treatment (range 10 mo to 15 y, mean+/-SD 6.86+/-3.92 y), the second group included 34 patients taking antiepileptic treatment (range 1-14 y, mean+/-SD 7.51+/-3.68 y) and the control group included 52 healthy children (range 4 mo to 15 y, mean+/-SD 6.94+/-3.92 y). Twelve-lead ECGs were obtained and heart rate, RR interval, P wave amplitude and duration, PR interval, QRS duration, QRS axis and QT intervals were measured, and QTc, QTd, QTcd were calculated in all subjects. The measurements were repeated in the first group under antiepileptic treatment. Results: While no significant difference in terms of heart rate, RR interval, P wave amplitude and duration, PR interval, QRS duration, QRS axis, QT intervals or QTc intervals was found, QTd and QTcd values were significantly increased in epileptic children compared with,the control group. QTd was 58.1+/-13.4 ms and 35.9+/-9.3 ms and QTcd was 91.0+/-22.9 and 68.6+/-18.0 ms in patients and controls, respectively. Antiepileptic treatment did not affect QT dispersion. Conclusion: QT dispersion is increased in epileptic children. Further investigation is needed to reveal the pathogenesis of myocardial repolarization abnormalities in epileptic patients.
Keywords: dysrhythmia; epilepsy; ion channels; QT dispersion; ventricular repolarization; LONG QT; ION CHANNELS; SEIZURES; DEATH; ABNORMALITIES; EPILEPSIES; DISORDERS; INTERVAL; MOUSE; BRAIN